(untitled) (Ozone Therapy Global Journal, 2012)
Legg-Calvé-Perthes disease (LCPD) is a necrosis of the femoral epiphysis that occurs during the growth stage and evolves in consecutive stages with varying degrees of intensity and extension. It is self-limited, caused by ischemia of unknown origin, and involves a complex course, from the time of diagnos is to the de cision of pr oviding treatment. The latter needs to be understood for it to be effective and delay or prevent the occurrence of the pain resulting from the arthrosis that may occur as a sequela.